Effect of tobramycin on protein synthesis in 2-deoxystreptamine aminoglycoside-resistant clinical isolates of Haemophilus influenzae. - Levy, J (1986)
Clinical isolates of Haemophilus influenzae resistant to a broad range of 2-deoxystreptamine aminoglycosides (2-DAM) were studied. The gene responsible for resistance could be mobilized by transformation into a 2-DAM susceptible laboratory strain of H. influenzae, enabling isogenic comparisons. The transformants had the same resistance phenotype as the parental strains. There was close linkage between 2-DAM resistance and streptomycin resistance, a chromosomal marker, but weak linkage between 2-DAM and erythromycin resistance. Resistant transformants exhibited a decreased accumulation of gentamicin due to the absence of the rapid, energy-dependent phase of uptake. Resistance was not through metabolic inactivation of the antibiotic; no aminoglycoside-acetylating, -adenylylating, or -phosphorylating activity was detected in the wild-type strains or in the 2-DAM-resistant transformants. Protein synthesis in 2-DAM-susceptible H. influenzae strains increased in the presence of low (1 microgram/ml) and moderate (50 micrograms/ml) concentrations of tobramycin. With higher concentrations (100 and 500 micrograms/ml), protein synthesis was progressively inhibited. In contrast, protein synthesis in 2-DAM-resistant clinical isolates and transformants was inhibited by 1 microgram of tobramycin per ml, and inhibition increased with higher drug concentrations. Since the stimulating effect of low concentrations of tobramycin in susceptible H. influenzae strains is probably due to misreading, these findings suggest that 2-DAM-resistant strains of H. influenzae have reduced sensitivity to misreading, indicating that altered ribosomes are responsible for the resistance.